MEMBANGUN KARAKTER ANAK USIA SEKOLAH DASAR MELALUI KETERAMPILAN BERBICARA - Yasinta Mahendra (Universitas Muhammadiyah Kotabumi, 2019)
Primary school age is the age of child growing that is the most important part of life. Children are like a sheet of white paper that will hold, and then saveall the scratches that are written on the paper. Likewise, children's memories, what children see will be stored in memory and will be imitated or even madeinto habits in life; this habit will grow into a character of the child later. In the Big Indonesian Dictionary, characters are interpreted as behavior or habits. Therefore, character becomes a very important thing to determine how a person behaves. The factors of character growth in child it self cannot beseparated from the role of parents and teachers as a major source of the role models for children. Errors in educating students that caused by the teachers can be dangerous for the process of children’s mental development. Of course, it will affect the character of the child. One of the bases for educating children is through courage, courage to be honest and courageous to speak up expressing things that become obstacles for children. Speaking skills are one of the media to build brave characters in elementary school-age children, by raising the ability to speak so that the child's mentality will be trained bravely. Especially, brave in expressing things or opinions that the children have from an early age. Therefore, it is hoped that intelligent, skilled, and brave generations will grow and have a strong character base in elementary school age children.